Unusual Presentation of Central Diabetes Insipidus in a Patient With Neurosarcoidosis - Vedha Sanghi MBBS; Aanchal Kapoor MD (SAGE Publishing, 2016)
Hypernatremia is a frequent cause of intensive care unit admission. The patient presented in this article had hypernatremia refractory to D5W (dextrose 5% water) therapy, which led to a complex investigation. Workup revealed central diabetes insipidus most likely secondary to flare up of neurosarcoidosis. The challenge in terms of diagnosis was a presentation with low urine output in the setting of hypernatremia resistant to treatment with desmopressin. This case unfolded the role of hypothyroidism causing secondary renal dysfunction and hence needed continued treatment with thyroxine in addition to treatment for hypernatremia.